Optimal vitamin D levels in Crohn's disease: a review. Issue 1 (11th December 2014) - Raftery, Tara; O'Sullivan, Maria
Abstract : Vitamin D deficiency is common among patients with Crohn's disease. Serum 25-hydroxyvitamin D (25(OH)D) is the best measure of an individual's vitamin D status and current cut-off ranges for sufficiency are debatable. Several factors contribute to vitamin D deficiency in Crohn's disease. These include inadequate exposure to sunlight, inadequate dietary intake, impaired conversion of vitamin D to its active metabolite, increased catabolism, increased excretion and genetic variants in vitamin D hydroxylation and transport. The effects of low 25(OH)D on outcomes other than bone health are understudied in Crohn's disease. The aim of the present review is to discuss the potential roles of vitamin D and the possible levels required to achieve them. Emerging evidence suggests that vitamin D may have roles in innate and adaptive immunity, in the immune-pathogenesis of Crohn's disease, prevention of Crohn's disease-related hospitalisations and surgery, in reducing disease severity and in colon cancer prevention. The present literature appears to suggest that 25(OH)D concentrations of ≥75 nmol/l may be required for non-skeletal effects; however, further research on optimal levels is required.